2009
DOI: 10.1007/s10765-009-0603-5
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical Properties of Sn–Ag–Cu Based Pb-Free Solders

Abstract: Lead-tin (Pb-Sn) alloys are the dominant solders used for electronic packaging because of their low cost and superior properties required for interconnecting electronic components. However, increasing environmental and health concerns over the toxicity of lead, combined with global legislation to limit the use of Pb in manufactured products, have led to extensive research and development studies of lead-free solders. The Sn-Ag-Cu ternary eutectic alloy is considered to be one of the promising alternatives. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Different thermal conductivity of the components (PCBs, Cu lead or electrical parts) composes different temperature gradients in the solder joint during solidification. Thermal conductivities of Sn-Ag-Cu alloys between 210 and 220 W m −1 K −1 were found by Kim et al [5] at room temperature. The highest thermal conductivity in this multi-component joint has Cu (386 W m −1 K −1 ), while the lowest thermal conductivity has one of the most commonly used PCB materials FR4 (0.2 W m −1 K −1 ).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Different thermal conductivity of the components (PCBs, Cu lead or electrical parts) composes different temperature gradients in the solder joint during solidification. Thermal conductivities of Sn-Ag-Cu alloys between 210 and 220 W m −1 K −1 were found by Kim et al [5] at room temperature. The highest thermal conductivity in this multi-component joint has Cu (386 W m −1 K −1 ), while the lowest thermal conductivity has one of the most commonly used PCB materials FR4 (0.2 W m −1 K −1 ).…”
Section: Introductionmentioning
confidence: 74%
“…1) for our Sn-Ag-Cu based alloys. In Kim et al, the work of [5], it was found that the thermal diffusivity of various Sn-Ag-Cu based alloys differs only marginally. It may be assumed that similar differences in the thermal diffusivity exist even for the liquid phases.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the analysis of several multi-component systems, two sets of alloys are potential substitutes for lead soldering. The first groups are the Sn-Ag-Cu (SAC) alloys with the addition of different metals (Bi, Zn, In and Sb) 16 . Previous studies have recommended the Sn-Ag-Cu-Bi quaternary system as a promising candidate for lead-free solders, as the biggest advantage of SnAgCuBi over welds SnAgCu is the lower melting temperature.…”
Section: Introductionmentioning
confidence: 99%